Method and apparatus for preparing composite quartz glass based on modified waste quartz glass powder

CN122685296BActive Publication Date: 2026-10-23CHANGFEI QUARTZ TECH (WUHAN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611193104.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-23
Estimated Expiration
2046-08-07

AI Technical Summary

Technical Problem

[0005]针对现有技术的缺陷,本申请的目的在于提供基于改性废石英玻璃粉制备复合石英玻璃的方法及装置,旨在解决现有工艺采用废石英玻璃直接回掺制备大尺寸的复合石英玻璃时,难以兼顾制品的表面质量与体相均匀性,易导致制品出现条纹、分层及微缺陷等问题,尤其适用于制备大尺寸(单边尺寸≥1000mm,厚度按实际生产要求设定)复合石英玻璃

Benefits of technology

(1)本申请提供的基于改性废石英玻璃粉制备复合石英玻璃的方法,通过废石英玻璃粉界面活化改性、改性废石英玻璃粉与高纯石英砂梯度配料、表层配料和芯层配料进行气电协同熔融,最后进行厚度自适应分段退火,通过各步骤的相互配合、协同作用,能够在复合石英玻璃制品的制备中提高废石英玻璃的循环利用比例,减小直接回掺造成的条纹、分层、开裂和表面缺陷风险,兼顾表面光洁度、内部均匀性和制品成型稳定性,从而制得大尺寸的复合石英玻璃,具有较好的经济效益和资源循环价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685296B_ABST
    Figure CN122685296B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of waste quartz glass recycling, and more particularly relates to a method and device for preparing composite quartz glass based on modified waste quartz glass powder. The application can improve the recycling proportion of waste quartz glass in the preparation of composite quartz glass products, reduce the risk of stripes, delamination, cracking and surface defects caused by direct back-doping, and take into account surface smoothness, internal uniformity and product forming stability, thereby preparing composite quartz glass, by intercoordination and synergistic effect of each step of interface activation modification of waste quartz glass powder, gradient batching of modified waste quartz glass powder and high-purity quartz sand, gas-electricity collaborative melting of surface layer batching and core layer batching, and thickness self-adaptive segmented annealing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of waste quartz glass recycling technology, and more specifically, relates to a method and apparatus for preparing composite quartz glass based on modified waste quartz glass powder. Background Technology

[0002] The current production of composite quartz glass typically uses high-purity quartz sand as the main raw material, resulting in a high dependence on high-purity raw materials and relatively high material costs. At the same time, quartz glass products generate a certain proportion of scrap and defective products during cutting, trimming, grinding, and finished product inspection. Directly discarding these would lead to resource waste and increase the pressure on solid waste treatment.

[0003] To address the aforementioned issues, existing technologies have attempted to achieve resource reuse through waste glass recycling, quartz powder re-addition, and the preparation of quartz glass via gas refining or electrofusion. However, in the context of composite quartz glass preparation, directly mixing waste quartz glass powder with high-purity quartz sand and then employing a single melting and conventional annealing process presents the following problems: First, during the melting of waste quartz glass and high-purity quartz sand, localized melting is asynchronous, and large temperature differences exist across the cross-section of large-sized products, making it difficult to simultaneously ensure the melting quality of the surface and core, easily leading to streaks, delamination, and micro-defects in the products. Second, the annealing process relies solely on experience; when product specifications (including thickness and dimensions) or the proportion of recycled waste quartz glass changes, it easily results in high residual stress, increased edge cracks, and a higher breakage rate.

[0004] Therefore, in the industrial-scale preparation of composite quartz glass, there is an urgent need to provide a preparation method that can increase the recycling rate of waste quartz glass, reduce the process fluctuations caused by direct re-doping, and take into account surface smoothness, internal uniformity and product molding stability, so as to meet the needs of industrial production. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the purpose of this application is to provide a method and apparatus for preparing composite quartz glass based on modified waste quartz glass powder. This method aims to solve the problems that arise when using existing processes to directly re-dope waste quartz glass to prepare large-size composite quartz glass, it is difficult to balance the surface quality and bulk uniformity of the product, which can easily lead to problems such as streaks, delamination, and micro-defects in the product. This method is particularly suitable for preparing large-size (single-sided dimension ≥1000mm, thickness set according to actual production requirements) composite quartz glass.

[0006] To achieve the above objectives, in a first aspect, this application provides a method for preparing composite quartz glass based on modified waste quartz glass powder, comprising the following steps: S1. Waste quartz glass powder is mixed with a composite modifier and then calcined to obtain modified waste quartz glass powder after interface activation modification treatment; wherein, the composite modifier includes Al2O3 and ZrO2. S2. The modified waste quartz glass powder and high-purity quartz sand are respectively formulated into surface layer material and core layer material; wherein, the mass fraction of modified waste quartz glass powder in the surface layer material is lower than the mass fraction of modified waste quartz glass powder in the core layer material. S3. The above-mentioned surface layer ingredients and the above-mentioned core layer ingredients are simultaneously fed into a composite melting device for melting; wherein, the above-mentioned surface layer ingredients are heated by gas refining, and the above-mentioned core layer ingredients are heated by electric melting. S4. The molten material, after being uniformly melted, is shaped and then subjected to segmented annealing to obtain composite quartz glass.

[0007] Preferably, in step S1, the mass ratio of Al2O3 to ZrO2 in the above composite modifier is 1:(0.8~1.2).

[0008] Preferably, the amount of the composite modifier is 2% to 3% of the mass of the waste quartz glass powder.

[0009] Preferably, the median particle size of the above-mentioned waste quartz glass powder is 75μm~150μm.

[0010] Preferably, the roasting temperature is 800℃~900℃ and the roasting time is 2h~3h.

[0011] Preferably, in step S2, the mass fraction of modified waste quartz glass powder in the surface layer ingredients is 15% to 20%, and the mass fraction of modified waste quartz glass powder in the core layer ingredients is 35% to 45%.

[0012] Preferably, the surface layer ingredients account for 16% to 36% of the total mass of the surface layer ingredients and the core layer ingredients.

[0013] Preferably, the median particle size of the surface layer material is 90μm~140μm, and the median particle size of the core layer material is 75μm~125μm.

[0014] Preferably, in step S2, the mass fraction of the modified quartz glass powder in the total ingredients is 30% to 40%.

[0015] Preferably, in step S3, the temperature of the gas refining heating is 1800℃~1850℃; and / or, The temperature for the above-mentioned electrofusion heating is 1700℃~1750℃.

[0016] Preferably, in step S4, during the segmented annealing process, the holding time corresponding to each 100°C decrease is 0.5h to 2.5h, and the holding time of the later segment is longer than that of the adjacent earlier segment; when the annealing temperature drops below 300°C, it is naturally cooled to room temperature with the furnace.

[0017] Secondly, this application provides a composite quartz glass, which is prepared by the above method.

[0018] Preferably, the thickness of the composite quartz glass is 20mm to 80mm.

[0019] Thirdly, this application provides a composite melting apparatus for preparing the above-mentioned composite quartz glass, comprising: A melting furnace body, wherein a molten pool is formed inside the melting furnace body, and the molten pool includes an upper surface layer region, a core layer region and a lower surface layer region from top to bottom along the thickness direction; The surface feeding channel is connected to the top and bottom of the melting furnace body and is used to feed the surface ingredients into the upper surface area and the lower surface area. The core layer feeding channel is connected to the middle side wall of the melting furnace body and is used to feed the core layer ingredients into the core layer area. A gas refining heating device is installed at the top and bottom of the above-mentioned melting furnace body for gas refining heating of the above-mentioned upper surface area and the above-mentioned lower surface area; An electrofusion heating device is arranged around the outside of the aforementioned melting furnace body for electrofusion heating of the aforementioned core layer region; A temperature measuring unit is used to monitor the temperature of the aforementioned upper surface layer area, the aforementioned core layer area, and the aforementioned lower surface layer area; The discharge port is located at the bottom of the aforementioned melting furnace body and is used to draw out the molten material after melting.

[0020] In summary, the technical solutions conceived in this application have the following main technical advantages compared with the prior art: (1) The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this application involves interface activation modification of waste quartz glass powder, gradient batching of modified waste quartz glass powder with high-purity quartz sand, surface batching and core batching for gas-electric synergistic melting, and finally thickness adaptive segmented annealing. Through the mutual cooperation and synergistic effect of each step, the recycling ratio of waste quartz glass can be increased in the preparation of composite quartz glass products, reducing the risk of stripes, delamination, cracking and surface defects caused by direct re-doping, and taking into account surface smoothness, internal uniformity and product molding stability, thereby producing large-size composite quartz glass with good economic benefits and resource recycling value.

[0021] (2) This application uses a composite modification system composed of Al2O3 and ZrO2 to perform interface activation modification on waste quartz glass powder and controls the ratio between the two modifiers. This enables the composite modifier to form a uniform and stable transition layer on its surface, improves the interfacial compatibility and high-temperature viscosity matching between waste quartz glass powder and high-purity quartz sand, and makes the silicon raw materials from different sources tend to be synchronized during the melting process. At the same time, it can improve the high-temperature structural stability, suppress local instability and the expansion of interface defects.

[0022] (3) Based on the cross-sectional structure of the target product, this application prepares modified waste quartz glass powder and high-purity quartz sand as surface material and core material respectively. The surface material adopts a lower recycling rate to ensure surface densification and smoothness, while the core material adopts a higher recycling rate to improve waste utilization. This can achieve coordination between surface quality and core waste utilization rate while ensuring overall recycling rate, effectively avoiding layered boundaries and surface defects.

[0023] (4) This application involves the combined gas-melting and electro-melting of the prepared surface and core materials. The surface material first forms a dense molten layer under gas-melting heating and then further densifies, improving surface smoothness. The core material achieves uniform bulk melting and maintains uniform temperature under electro-melting heating. The uniformly melted molten body is then shaped and subjected to segmented annealing. The holding time of each segment gradually increases with the number of annealing segments, which allows the thermal stress to be released layer by layer from the outside to the inside in the thickness direction, avoiding cracks caused by the inability to release the thermal stress in the core in time due to excessively rapid cooling rate. Attached Figure Description

[0024] Figure 1 This is a schematic flowchart of the method for preparing composite quartz glass based on modified waste quartz glass powder provided in this application; Figure 2 This is a schematic diagram of the preparation process of the modified waste quartz glass powder provided in this application; Figure 3 This is a schematic diagram of the composite melting device provided in the embodiments of this application; In all the accompanying drawings, the same reference numerals are used to denote the same elements or structures, wherein: 1 is the melting furnace body; 2 is the molten pool; 3 is the surface feeding channel; 4 is the core feeding channel; 5 is the gas refining heating device; 6 is the electric melting heating device; 7 is the temperature measuring unit; 8 is the discharge port; 21 is the upper surface layer area; 22 is the core layer area; 23 is the lower surface layer area. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0026] In the description of this application, it should be understood that the term "and / or" describes a relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The symbol " / " in this document indicates that the related objects are in an "or" relationship; for example, A / B means A or B.

[0027] In the description of the embodiments in this application, the words "exemplary" or "for example" are used to indicate that they are examples, illustrations, or descriptions. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of this application should not be construed as being more preferred or advantageous than other embodiments or design options. Specifically, the use of the words "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.

[0028] In the description of the embodiments of this application, unless otherwise stated, "multiple" means two or more.

[0029] This application provides a method for preparing composite quartz glass based on modified waste quartz glass powder, such as... Figure 1 As shown, it includes the following steps: S1. Waste quartz glass powder is mixed with a composite modifier and then calcined to obtain modified waste quartz glass powder after interface activation modification treatment; wherein, the composite modifier includes Al2O3 and ZrO2. S2. The modified waste quartz glass powder and high-purity quartz sand are respectively formulated into surface layer material and core layer material; wherein, the mass fraction of modified waste quartz glass powder in the surface layer material is lower than the mass fraction of modified waste quartz glass powder in the core layer material. S3. The above-mentioned surface layer ingredients and the above-mentioned core layer ingredients are simultaneously fed into a composite melting device for melting; wherein, the above-mentioned surface layer ingredients are heated by gas refining, and the above-mentioned core layer ingredients are heated by electric melting. S4. The molten material, after being uniformly melted, is shaped and then subjected to segmented annealing to obtain composite quartz glass.

[0030] This application does not impose any particular restriction on the source of the aforementioned waste quartz glass powder. It can be obtained through processing scraps and defective products generated during the cutting, trimming, grinding, and finished product inspection of quartz glass products, or it can be commercially available waste quartz glass powder products. In some embodiments, this application directly uses scraps or defective products from quartz glass products as raw materials, which reduces the consumption of high-purity quartz sand and the emission of solid waste, thereby achieving the resource-based recycling of waste quartz glass.

[0031] In some embodiments, the processing method for waste quartz glass powder obtained from scraps or substandard products is as follows: the waste quartz glass is sorted, and after removing obvious inclusions, it is sequentially washed, crushed, ground, and graded to obtain waste quartz glass powder. Washing is used to remove surface contaminants (such as oil, dust, metal fragments, etc.), crushing and grinding are used to process the blocky waste quartz glass into powder, and grading is used to control the particle size distribution of the powder to ensure uniform loading and sufficient reaction of the composite modifier on the surface of the waste quartz glass powder during subsequent modification treatment. More preferably, after grading, magnetic separation and pure water rinsing can be used to further reduce metallic impurities and surface-attached impurities, thereby improving the purity of the waste quartz glass powder.

[0032] In this application, the composite modifier is a combination of Al2O3 and ZrO2, which can improve the interfacial compatibility and high-temperature viscosity matching between waste quartz glass powder and virgin quartz sand, making the siliceous raw materials from different sources tend to synchronize during the melting process, while improving high-temperature structural stability and suppressing local instability and the propagation of interfacial defects. Through the synergistic effect of the two, interfacial compatibility and high-temperature stability are simultaneously achieved.

[0033] In some embodiments, in step S1, the mass ratio of Al2O3 to ZrO2 in the composite modifier is 1:(0.8~1.2), such as 1:0.8, 1:0.9, 1:1, 1:1.2, etc., which can ensure that the composite modifier forms a uniform and stable transition layer on the surface of waste quartz glass powder. When the proportion of Al2O3 is too high, it will lead to higher system viscosity and an increased risk of local crystallization; when the proportion of ZrO2 is too high, it will lead to difficulty in dispersing the modifier and the appearance of local unmelted particles or uneven interfaces.

[0034] In some embodiments, the amount of the composite modifier is 2% to 3% of the mass of the waste quartz glass powder, which can ensure sufficient modification while avoiding the adverse effects of excessive addition of modifier.

[0035] In some embodiments, the median particle size of the waste quartz glass powder is 75μm~150μm, which helps to ensure uniform loading and full reaction of the composite modifier on the particle surface during subsequent modification. At the same time, it can improve the particle size matching and melting synchronization between the waste quartz glass powder and high-purity quartz sand during the melting process.

[0036] It is understood that this application does not have any particular limitation on the mixing method of waste quartz glass powder and composite modifier. Dry mixing can be carried out using mixing equipment such as V-type mixers, double cone mixers, three-dimensional motion mixers, or low-speed ribbon mixers. In some embodiments, before mixing, the waste quartz glass powder is preferably dried at 100℃~140℃ for 1h~2h to reduce the surface adsorbed water content and avoid agglomeration of the modified components.

[0037] In some embodiments, the calcination temperature is 800℃~900℃ and the calcination time is 2h~3h, which enables the composite modifier to form a uniform and stable transition layer on the surface of waste quartz glass powder, which is beneficial to improving the interfacial compatibility between waste quartz glass powder and new quartz sand during the subsequent melting process.

[0038] The inventors of this application discovered in actual production that if the same proportion of recycled waste quartz glass powder (i.e., the mass fraction of modified waste quartz glass powder) is used in the surface layer and core layer of the target product, the quality requirements of the surface and core layers of the resulting composite quartz glass cannot be simultaneously met. Based on the above discovery, this application sets the mass fraction of modified waste quartz glass powder in the surface layer and core layer materials respectively, with a lower mass fraction of modified quartz glass powder in the surface layer and a higher mass fraction of modified quartz glass powder in the core layer.

[0039] In some embodiments, the modified waste quartz glass powder in the surface layer ingredients is 15% to 20% by mass, and the modified waste quartz glass powder in the core layer ingredients is 35% to 45% by mass. By rationally allocating the recycling ratio of modified waste quartz glass powder between the surface layer ingredients and the core layer ingredients, it is helpful to achieve coordination between surface layer quality and core layer waste utilization rate.

[0040] In some embodiments, the mass fraction of the modified waste quartz glass powder in the total batch (surface batch + core batch) is 30% to 40%. By controlling the overall recycling rate of the modified waste quartz glass powder at 30% to 40%, a high recycling rate of waste quartz glass powder can be ensured, while providing sufficient surface space for the composite modifier and avoiding the problem of increased interface defects caused by an excessively high proportion of waste quartz glass powder.

[0041] In some embodiments, the surface layer material accounts for 16% to 36% of the total mass of the surface layer material and the core layer material, that is, the mass ratio of the surface layer material to the core layer material is 0.16:0.84 to 0.36:0.64. By controlling the mass ratio of the surface layer material and the core layer material within this range, the surface layer material accounts for a smaller proportion of the total material, thus ensuring the densification of the surface of the composite quartz glass and the control of defects; the core layer material accounts for a larger proportion of the total material, which provides sufficient material preparation space for the recycling of waste quartz glass powder. Through the reasonable allocation of the surface layer material and the core layer material in the proportion of the material, the cross-sectional functional zoning of large-size composite quartz glass can be effectively realized.

[0042] In some embodiments, in step S3, the surface layer and core layer materials are simultaneously fed into a composite melting device for melting. In some embodiments, the surface layer materials are heated using gas refining, utilizing a high-temperature gas refining flame to rapidly heat the surface area, which facilitates melting and further densification of the surface layer materials, thereby improving surface finish. In some embodiments, the gas refining heating temperature is 1800℃~1850℃. In some embodiments, the core layer materials are heated using electrofusion, utilizing electromagnetic induction or electrothermal action to heat the core area as a whole, which facilitates full and uniform melting of the core layer bulk phase and maintains temperature uniformity. In some embodiments, the electrofusion heating temperature is 1700℃~1750℃. Through the synergistic effect of surface gas refining heating and core electrofusion heating, a differentiated thermal field distribution can be formed in the thickness direction of large-size products, allowing the surface and core layers to obtain suitable melting conditions, thereby simultaneously ensuring both surface quality and internal uniformity of large-size products.

[0043] In some embodiments, the temperature difference between the gas refining heating and the electrofusion heating is 50°C to 150°C. Further, considering the surface densification effect, interlayer transition continuity, and residual stress control, it is preferable to control the temperatures of the gas refining heating and electrofusion heating within the range of 50°C to 120°C. During specific equipment commissioning, the target temperature difference between the surface layer and the core layer can be achieved and maintained by adjusting the heat input to the gas refining zone and the electrofusion zone.

[0044] Based on the functional requirements of the surface layer and core layer of the composite quartz glass, this application sets different heating methods and heating temperatures, and by adjusting the mass ratio of the surface layer material to the core layer material, combined with the above-mentioned differentiated melting process, the ratio of the surface layer thickness to the core layer thickness after molding falls within the range of 2φ:(1-2φ).

[0045] In some embodiments, the median particle size of the surface layer material is 90μm to 140μm, and the median particle size of the core layer material is 75μm to 125μm. This is beneficial to ensure particle size matching and melting synchronization between the two during the melting process, so that the surface layer material and the core layer material can achieve full and uniform melting under their respective thermal field conditions.

[0046] In some embodiments, in step S4, the melt that has been uniformly melted is led out through the outlet and then subjected to a forming process, so that the high-temperature melt is transformed from a liquid state into a solid blank with a target cross-sectional shape and size, providing a blank basis for the subsequent annealing and final processing of large-size composite quartz glass.

[0047] In some embodiments, the forming methods described above include, but are not limited to, calendering or compression molding. Calendering is suitable for preparing plate-shaped or ingot-shaped products. Pressure is applied to the melt using calendering rollers, and its thickness is controlled, causing the melt to flatten and solidify under pressure, forming a plate-shaped blank with uniform thickness. Compression molding is suitable for preparing products with specific contours or curved surfaces. The melt is introduced into a mold cavity and filled under pressure, forming a blank with the target shape. An appropriate forming method can be selected according to the shape and size requirements of the target product to meet the forming needs of large-sized composite quartz glass products of different shapes.

[0048] In some embodiments, in step S4, during the segmented annealing process, the holding time corresponding to each 100°C decrease is 0.5h to 2.5h, and the holding time of the later segment is longer than that of the adjacent earlier segment; when the annealing temperature drops below 300°C, it is naturally cooled to room temperature with the furnace.

[0049] By adopting segmented annealing and delaying the holding time of each segment, the thermal stress of large-sized composite quartz glass products can be released layer by layer from the outside to the inside in the thickness direction, avoiding the occurrence of cracks at the edge due to the inability to release the thermal stress in the core in time because the cooling rate is too fast.

[0050] In some embodiments, the preferred starting temperature for the segmented annealing is 1150℃ to 1200℃. This temperature range is close to the stress release sensitive zone of quartz glass, enabling the preform to effectively release internal thermal stress before entering the segmented cooling process, thereby laying the foundation for layer-by-layer stress release during subsequent segmented annealing. It should be understood that, without departing from the technical concept of this application, the starting annealing temperature can be appropriately adjusted according to the product specifications and the temperature of the preform after molding, all within the protection scope of this application.

[0051] In some embodiments, the segmented annealing includes at least eight stages, wherein the holding time for the first stage of annealing is 45-90 minutes, the holding time for the second stage of annealing is 50-100 minutes, the holding time for the third stage of annealing is 60-110 minutes, the holding time for the fourth stage of annealing is 65-115 minutes, the holding time for the fifth stage of annealing is 70-120 minutes, the holding time for the sixth stage of annealing is 75-125 minutes, the holding time for the seventh stage of annealing is 80-130 minutes, and the holding time for the eighth stage of annealing is 90-140 minutes, with each subsequent stage having a longer holding time than the preceding stage. Optionally, the segmented annealing also includes a ninth stage of annealing, wherein the holding time for the ninth stage of annealing is 95-150 minutes.

[0052] The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this application firstly involves interfacial activation modification treatment of the waste quartz glass powder, enabling the composite modifier to form a uniform and stable transition layer on its surface. This improves the interfacial compatibility and high-temperature viscosity matching between the waste quartz glass powder and high-purity quartz sand, allowing siliceous raw materials from different sources to tend to synchronize during subsequent melting. Next, through gradient feeding, the surface layer uses modified waste quartz glass powder with a lower recycling rate to ensure surface densification and smoothness, while the core layer uses modified waste quartz glass powder with a higher recycling rate to improve the overall utilization rate of the waste. Subsequently, through gas-electric synergistic melting, the surface layer materials achieve rapid densification under gas heating, while the core layer materials achieve uniform melting under electric heating, forming a differentiated thermal field distribution along the thickness direction of large-size products, thus simultaneously ensuring surface quality and internal uniformity. Finally, through segmented annealing, the internal thermal stress of the product is released layer by layer, avoiding the problems of high residual stress, increased edge cracks, and increased breakage rate caused by direct cooling. The above steps work together and synergistically to increase the recycling rate of waste quartz glass in the preparation of composite quartz glass products, reduce the risk of streaks, delamination, cracking and surface defects caused by direct re-doping, and take into account surface smoothness, internal uniformity and product molding stability, thereby producing large-size composite quartz glass.

[0053] Based on this, this application also protects a composite quartz glass prepared by the above method.

[0054] In some embodiments, the total thickness of the composite quartz glass is 20mm to 80mm, preferably 30mm to 60mm, and more preferably 30mm to 40mm.

[0055] On the other hand, this application also provides a composite melting apparatus for preparing the above-mentioned composite quartz glass, comprising: A melting furnace body, wherein a molten pool is formed inside the melting furnace body, and the molten pool includes an upper surface layer region, a core layer region and a lower surface layer region from top to bottom along the thickness direction; The surface feeding channel is connected to the top and bottom of the melting furnace body and is used to feed the surface ingredients into the upper surface area and the lower surface area. The core layer feeding channel is connected to the middle side wall of the melting furnace body and is used to feed the core layer ingredients into the core layer area. A gas refining heating device is installed at the top and bottom of the above-mentioned melting furnace body for gas refining heating of the above-mentioned upper surface area and the above-mentioned lower surface area; An electrofusion heating device is arranged around the outside of the aforementioned melting furnace body for electrofusion heating of the aforementioned core layer region; A temperature measuring unit is used to monitor the temperature of the aforementioned upper surface layer area, the aforementioned core layer area, and the aforementioned lower surface layer area; The discharge port is located at the bottom of the aforementioned melting furnace body and is used to draw out the molten material after melting.

[0056] In some embodiments, the gas refining heating device includes, but is not limited to, gas refining nozzles. The number and location of the gas refining heating device can be configured according to the structure of the melting furnace and the size requirements of large-sized products. For example, one or more gas refining nozzles can be installed at the top and bottom of the melting furnace to heat the upper and lower surface areas of the molten pool respectively. The gas refining heating device generates a high-temperature flame by burning combustible gas, directly heating the surface of the molten material, promoting densification of the surface molten material, and improving surface finish. In some embodiments, the gas refining nozzle is an oxyhydrogen flame gas refining nozzle.

[0057] In some embodiments, the electrofusion heating device includes, but is not limited to, electrofusion induction coils. The number and distribution of the electrofusion heating devices can be selected according to the volume of the core layer and the requirements for heating uniformity. For example, one or more electrofusion induction coils can be arranged along the height of the core layer on the outside of the melting furnace body to perform overall electrofusion heating of the core layer. The electrofusion heating device generates an alternating electromagnetic field through a high-frequency alternating current, inducing eddy currents in the molten core layer and using the thermal effect of the eddy currents to heat the core, ensuring that the core bulk phase is fully melted and maintaining a uniform temperature. In some embodiments, the electrofusion induction coil is a high-frequency induction coil.

[0058] It should be understood that the materials, reagents, and instruments used in the following embodiments, as long as they are of the same or similar type, model, quality, properties, or functions, can be used to implement this application. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.

[0059] The following are examples and comparative examples: Example 1 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this embodiment includes the following steps: (1) Preparation of modified waste quartz glass powder Waste quartz glass scraps are cleaned to remove surface contaminants, then crushed, ground, and graded. Magnetic separation and pure water rinsing further reduce metallic and surface impurities, yielding waste quartz glass powder. This powder is then mixed with a composite modifier and calcined in a furnace to obtain modified waste quartz glass powder (process as follows). Figure 2 (As shown).

[0060] In this embodiment, the median particle size D50 of the waste quartz glass powder is 120 μm, the mass ratio of Al2O3 to ZrO2 in the composite modifier is 1:1, the amount of composite modifier is 2.4% of the mass of the waste quartz glass powder, the calcination temperature is 850℃, and the calcination time is 2.5 h.

[0061] (2) Preparation of surface layer ingredients and core layer ingredients Modified waste quartz glass powder and high-purity quartz sand were separately formulated into surface layer and core layer materials, with a total material weight of 1000 kg.

[0062] In this embodiment, the mass fraction of modified waste quartz glass powder in the surface layer is limited to 17.5%, and the mass fraction of modified waste quartz glass powder in the core layer is limited to 40.5%. The surface layer accounts for 24% of the total mass of the ingredients, i.e., the mass ratio of the surface layer to the core layer is 0.24:0.76, and the mass fraction of modified waste quartz glass powder in the total ingredients is 35%. The median particle size of the surface layer is approximately 110 μm, and the median particle size of the core layer is approximately 95 μm. Specifically, 240 kg of surface layer ingredients includes 42 kg of modified waste quartz glass powder and 198 kg of high-purity quartz sand, and 760 kg of core layer ingredients includes 308 kg of modified waste quartz glass powder and 452 kg of high-purity quartz sand.

[0063] (3) Gas-electric synergistic composite melting A schematic diagram of the composite melting device used in this application is shown below. Figure 3 As shown, the furnace includes a melting furnace body 1, a molten pool 2, a surface feeding channel 3, a core feeding channel 4, a gas refining heating device 5, an electro-melting heating device 6, a temperature measuring unit 7, and a discharge port 8. The molten pool 2 includes an upper surface layer 21, a core layer 22, and a lower surface layer 23. The gas refining heating device 5 is located at the top and bottom of the melting furnace body 1 and is used to heat the upper surface layer 21 and the lower surface layer 23 through gas refining. The electro-melting heating device 6 is arranged around the outside of the melting furnace body 1 and is used to electro-melt heat the core layer 22.

[0064] The surface materials are fed into the top and bottom of the melting furnace 1 through the surface feeding channel 3, and then into the upper surface zone 21 and lower surface zone 23 of the molten pool 2. The core materials are fed into the middle of the melting furnace 1 through the core feeding channel 4, and then into the core zone 22 of the molten pool 2. The surface zone is provided with a gas refining heat source by the gas refining heating device 5, and the core zone is electrically heated by the electro-melting heating device 6. The temperature is monitored in real time by the temperature measuring unit 7. Finally, the uniformly molten material is led out through the discharge port 8.

[0065] Specifically, in this embodiment, the surface layer is heated by gas refining using an oxyhydrogen flame, with the temperature controlled at around 1830°C; the core layer is heated by electrofusion using high-frequency induction melting, with the temperature controlled at around 1725°C, meaning the temperature difference between the surface and core layers is approximately 105°C.

[0066] (4) Molding and segmented annealing The melt is rolled into ingot blanks, which are then sent to an annealing furnace for segmented annealing and cooling starting at 1200℃, with each segmented annealing being held at 100℃ for a period of time.

[0067] The holding time for the first annealing stage (1200℃~1100℃) is 60 min; the holding time for the second annealing stage (1100℃~1000℃) is 65 min; the holding time for the third annealing stage (1000℃~900℃) is 70 min; the holding time for the fourth annealing stage (900℃~800℃) is 75 min; the holding time for the fifth annealing stage (800℃~700℃) is 80 min; the holding time for the sixth annealing stage (700℃~600℃) is 85 min; the holding time for the seventh annealing stage (600℃~500℃) is 95 min; the holding time for the eighth annealing stage (500℃~400℃) is 100 min; and the holding time for the ninth annealing stage (400℃~300℃) is 105 min. After that, the furnace is allowed to cool naturally to room temperature.

[0068] After annealing, a composite quartz glass with dimensions of 1500mm×1200mm×30mm is obtained, with a single-sided surface layer thickness of 3.6mm.

[0069] Comparative Example 1 This comparative example uses a conventional process to prepare composite quartz glass from waste quartz glass powder, including the following steps: 350 kg of unmodified waste quartz glass powder and 650 kg of high-purity quartz sand were mixed evenly to obtain the total batch. Then, a conventional electric melting method was used as the single heat source to melt the total batch at a melting temperature of 1740℃. The melt was rolled into ingot blanks, which were then sent to an annealing furnace for integral annealing. Specifically, the furnace was held at 1180℃ for 2 hours, then cooled to 900℃ at a rate of 10℃ / h, and then further cooled to 600℃ at a rate of 20℃ / h, before being allowed to cool naturally to room temperature. After annealing, large-size ingot products, i.e., composite quartz glass, were obtained.

[0070] Comparative Example 2 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this comparative example is the same as that in Example 1, except that the modifier in step (1) is only Al2O3.

[0071] Comparative Example 3 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this comparative example is the same as that in Example 1, except that the modifier in step (1) is only ZrO2.

[0072] Comparative Example 4 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this comparative example is the same as that in Example 1, except that the mass ratio of Al2O3 and ZrO2 in the composite modifier in step (1) is 1:0.5.

[0073] Comparative Example 5 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this comparative example is the same as that in Example 1, except that the mass ratio of Al2O3 and ZrO2 in the composite modifier in step (1) is 1:1.5.

[0074] Comparative Example 6 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this comparative example is the same as that in Example 1, except that the mass fraction of modified waste quartz glass powder in the surface layer and the mass fraction of modified waste quartz glass powder in the core layer are both 35% in step (2).

[0075] Comparative Example 7 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this comparative example is the same as that in Example 1, except that: in step (2), the mass fraction of modified waste quartz glass powder in the surface layer is 40.5%, and the mass fraction of modified waste quartz glass powder in the core layer is 17.5%.

[0076] Comparative Example 8 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this comparative example is the same as that in Example 1, except that: in step (2), the mass fraction of modified waste quartz glass powder in the surface layer is 10%, and the mass fraction of modified waste quartz glass powder in the core layer is about 43%.

[0077] Comparative Example 9 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this comparative example is the same as that in Example 1, except that: in step (2), the mass fraction of modified waste quartz glass powder in the surface layer is 30%, and the mass fraction of modified waste quartz glass powder in the core layer is about 36.6%.

[0078] The properties of the composite quartz glasses prepared in Example 1 and Comparative Examples 1-9 were tested and evaluated. The test items and evaluation criteria are as follows: a. Apparent layering: Classified into levels 0 to 3, where level 0 is no visible layering; level 1 is a localized slight layered boundary; level 2 is a clear layered transition line; and level 3 is continuous layering or localized cracking.

[0079] b. Number of visible defects: Counted per 100cm 2 The number of visible defects (including streaks, white spots, and unmelted particles).

[0080] c. Edge cracking: Count the number of micro-cracks on the edge of each product after annealing.

[0081] d. Interlayer transition continuity: Take a cross-section along the thickness direction of the product, polish it, and then perform optical microscopic observation; focus on observing whether there are continuous layered boundaries, obvious interface fracture zones, or striation aggregation zones in the surface / core layer interface area. Then classify it into levels 1 to 4, where level 1 is the presence of a continuous and clear interface or obvious fracture zone; level 2 is a local interface interruption with relatively obvious layered boundaries; level 3 is a basically continuous interface with only local weak striation transitions; level 4 is the absence of obvious layered interfaces with a continuous and natural transition.

[0082] e. Residual stress level: The stress birefringence method is used for detection and it is graded from 1 to 4. Grade 1 is low, with very weak stress fringes; Grade 2 is relatively low, with local weak stress fringes visible; Grade 3 is relatively high, with obvious stress fringes; Grade 4 is high, with strong stress concentration or obvious stress spots.

[0083] The test results are shown in Table 1.

[0084]

[0085] Test results show that the composite quartz glass produced by Comparative Example 1 using the traditional recycling process (no interface activation modification + uniform mixing + single melting + conventional annealing) has an apparent delamination level of 3 and a visible defect count of 14 per 100cm. 2 The original sample exhibited 7 microcracks per piece at the edges, a layer transition continuity of level 1, and a residual stress level of level 4, demonstrating significant delamination, numerous defects, and high residual stress. In contrast, the embodiments of this application, through a synergistic design of interface activation modification, gradient feeding, gas-electric synergistic melting, and thickness-adaptive segmented annealing, with each step working in concert, resulted in a composite quartz glass with an apparent delamination level of 0 and a visible defect count of 2 per 100cm. 2 The number of edge microcracks was 1 per piece, the interlayer transition continuity was level 4, and the residual stress level was level 1. These results demonstrate that this application can significantly reduce the risk of delamination, striations, cracking, and surface defects in composite quartz glass, while maintaining surface smoothness, internal uniformity, and product molding stability. Simultaneously, it increases the recycling rate of waste quartz glass, demonstrating good economic benefits and resource recycling value.

[0086] Example 2 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this embodiment is the same as in Embodiment 1, except that: In step (1), the mass ratio of Al2O3 to ZrO2 in the composite modifier is 1:0.8, the calcination temperature is 800℃, and the calcination time is 2h.

[0087] In step (2), the mass fraction of modified waste quartz glass powder in the surface layer is 15%, the mass fraction of modified waste quartz glass powder in the core layer is about 36.4%, and the surface layer accounts for 30% of the total mass of the ingredients. That is, the mass ratio of the surface layer ingredients to the core layer ingredients is 0.3:0.7, and the mass fraction of modified waste quartz glass powder in the total ingredients is 30%.

[0088] In step (3), the temperature of gas refining heating is controlled at around 1800℃; the temperature of electric melting heating is controlled at around 1740℃, that is, the temperature difference between the surface layer and the core layer is about 60℃.

[0089] After annealing, a composite quartz glass with dimensions of 1500mm×1200mm×30mm is obtained, with a single-sided surface layer thickness of 4.5mm.

[0090] Example 3 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this embodiment is the same as in Embodiment 1, except that: Step (1): The mass ratio of Al2O3 to ZrO2 in the composite modifier is 1:1.2, the calcination temperature is 900℃, the calcination time is 3h, and the amount of composite modifier is 2% of the mass of waste quartz glass powder.

[0091] In step (2), the mass fraction of modified waste quartz glass powder in the surface layer is 20%, the mass fraction of modified waste quartz glass powder in the core layer is 43.8%, and the surface layer accounts for 16% of the total mass of the ingredients. That is, the mass ratio of the surface layer ingredients to the core layer ingredients is 0.16:0.84, and the mass fraction of modified waste quartz glass powder in the total ingredients is 40%.

[0092] In step (3), the temperature of gas refining heating is controlled at around 1850℃; the temperature of electric melting heating is controlled at around 1730℃, that is, the temperature difference between the surface layer and the core layer is about 120℃.

[0093] After annealing, a composite quartz glass with dimensions of 1500mm×1200mm×40mm was obtained, with a single-sided surface layer thickness of 3.2mm.

[0094] Example 4 The method for preparing composite quartz glass based on modified waste quartz glass powder provided in this embodiment includes the following steps: (1) Refer to step (1) of Example 1 to prepare modified waste quartz glass powder Specifically, in this embodiment, the median particle size D50 of the waste quartz glass powder is 110 μm, the mass ratio of Al2O3 to ZrO2 in the composite modifier is 1:1, and the amount of composite modifier used is 3% of the mass of the waste quartz glass powder.

[0095] (2) Refer to step (2) of Example 1 to prepare the surface layer ingredients and core layer ingredients. The modified waste quartz glass powder accounts for 16.64% of the mass of the surface layer ingredients and 35.84% of the mass of the core layer ingredients. The surface layer ingredients account for 20% of the total mass of the ingredients, that is, the mass ratio of the surface layer ingredients to the core layer ingredients is 0.2:0.8, and the mass fraction of the modified waste quartz glass powder in the total ingredients is 32%.

[0096] (3) Perform composite melting according to step (3) of Example 1. In this embodiment, the temperature of the gas refining heating in the surface zone is controlled at around 1825°C; the temperature of the electrofusion heating in the core zone is controlled at around 1730°C, that is, the temperature difference between the surface and the core is about 95°C.

[0097] (4) Perform molding and segmented annealing according to step (4) of Example 1. In this embodiment, the formed blank is annealed and cooled in stages starting from 1180°C, and the staged annealing is carried out by holding the temperature for 100°C every time the temperature drops. The holding time for the first stage of annealing (1180℃~1080℃) is 65 min; the holding time for the second stage of annealing (1080℃~980℃) is 70 min; the holding time for the third stage of annealing (980℃~880℃) is 75 min; the holding time for the fourth stage of annealing (880℃~780℃) is 80 min; the holding time for the fifth stage of annealing (780℃~680℃) is 85 min; the holding time for the sixth stage of annealing (680℃~580℃) is 95 min; the holding time for the seventh stage of annealing (580℃~480℃) is 100 min; the holding time for the eighth stage of annealing (480℃~380℃) is 105 min; and the holding time for the ninth stage of annealing (380℃~280℃) is 110 min.

[0098] After annealing, a composite quartz glass window with an equivalent diameter of 600 mm and a thickness of 40 mm is obtained, with a single-sided surface layer thickness of 4 mm.

[0099] The properties of the composite quartz glasses prepared in Examples 2-4 were tested using the same test methods and evaluation criteria as in Example 1. The test results are shown in Table 2.

[0100]

[0101] The test results (Table 2) show that the composite quartz glasses prepared in Examples 2-4 all exhibit excellent interfacial compatibility, surface densification, and internal uniformity, with an apparent delamination level of 0 and a visible defect count of no more than 3 per 100cm. 2The number of edge microcracks does not exceed 2 per piece, the interlayer transition continuity is level 4, and the residual stress level is level 1. These results demonstrate that the method for preparing composite quartz glass based on modified waste quartz glass provided in this application can achieve excellent product quality under different product forms (e.g., window pieces, covers, block blanks), different product specifications (H values), and different cross-sectional structures (φ values), exhibiting good process adaptability and broad industrial application prospects.

[0102] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing composite quartz glass based on modified waste quartz glass powder, characterized in that, Includes the following steps: S1. Waste quartz glass powder is mixed with a composite modifier and then calcined to obtain modified waste quartz glass powder after interface activation modification treatment; wherein, the composite modifier includes Al2O3 and ZrO2, and the mass ratio of Al2O3 to ZrO2 is 1:(0.8~1.2). S2. The modified waste quartz glass powder and high-purity quartz sand are respectively formulated into a surface layer material and a core layer material; the mass fraction of modified waste quartz glass powder in the surface layer material is 15%~20%, the mass fraction of modified waste quartz glass powder in the core layer material is 35%~45%, and the surface layer material accounts for 16%~36% of the total mass of the surface layer material and the core layer material; S3. The surface layer ingredients and the core layer ingredients are simultaneously fed into a composite melting device for melting; wherein, the surface layer ingredients are heated by gas refining at a temperature of 1800℃~1850℃; the core layer ingredients are heated by electrofusion at a temperature of 1700℃~1750℃. S4. The molten material, after being uniformly melted, is shaped and then subjected to segmented annealing to obtain composite quartz glass.

2. The method according to claim 1, characterized in that, The amount of the composite modifier is 2% to 3% of the mass of the waste quartz glass powder; and / or, The median particle size of the waste quartz glass powder is 75μm~150μm; And / or, The roasting temperature is 800℃~900℃, and the roasting time is 2h~3h.

3. The method according to claim 1, characterized in that, The mass fraction of the modified waste quartz glass powder in the total ingredients is 30%~40%.

4. The method according to claim 1, characterized in that, In step S4, during the segmented annealing process, the holding time corresponding to each 100°C drop is 0.5h to 2.5h, and the holding time of the later segment is longer than that of the adjacent earlier segment; when the annealing temperature drops below 300°C, it is naturally cooled to room temperature with the furnace.

5. A composite quartz glass, characterized in that, The composite quartz glass is prepared by the method described in any one of claims 1 to 4.

6. The composite quartz glass according to claim 5, characterized in that, The thickness of the composite quartz glass is 20mm to 80mm.

7. A composite melting apparatus for preparing the composite quartz glass as described in claim 5 or 6, characterized in that, include: A melting furnace body (1) is formed inside the melting furnace body. The melting pool (2) includes an upper surface layer region (21), a core layer region (22) and a lower surface layer region (23) in the thickness direction from top to bottom. The surface feeding channel (3) is connected to the top and bottom of the melting furnace body (1) and is used to feed the surface ingredients into the upper surface area (21) and the lower surface area (23). The core layer feeding channel (4) is connected to the middle side wall of the melting furnace body (1) and is used to feed the core layer ingredients into the core layer area (22). Gas refining heating device (5) is installed at the top and bottom of the melting furnace body (1) for gas refining heating of the upper surface zone (21) and the lower surface zone (23); An electrofusion heating device (6) is arranged around the outside of the melting furnace body (1) for electrofusion heating of the core layer area (22); Temperature measuring unit (7) is used to monitor the temperature of the upper surface layer (21), the core layer (22) and the lower surface layer (23); The discharge port (8) is located at the bottom of the melting furnace body (1) and is used to draw out the molten material after melting.

Citation Information

Patent Citations

  • Method for preparing high-purity quartz materials by using tailing materials

    CN109437551A

  • Quartz glass preparation method using quartz powder as raw material and quartz product

    CN120289069A